If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + 4 = 7(x + -4) Reorder the terms: 4 + -12x = 7(x + -4) Reorder the terms: 4 + -12x = 7(-4 + x) 4 + -12x = (-4 * 7 + x * 7) 4 + -12x = (-28 + 7x) Solving 4 + -12x = -28 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 4 + -12x + -7x = -28 + 7x + -7x Combine like terms: -12x + -7x = -19x 4 + -19x = -28 + 7x + -7x Combine like terms: 7x + -7x = 0 4 + -19x = -28 + 0 4 + -19x = -28 Add '-4' to each side of the equation. 4 + -4 + -19x = -28 + -4 Combine like terms: 4 + -4 = 0 0 + -19x = -28 + -4 -19x = -28 + -4 Combine like terms: -28 + -4 = -32 -19x = -32 Divide each side by '-19'. x = 1.684210526 Simplifying x = 1.684210526
| 306-x=200 | | 8t+4t=-12 | | 5+2(3G-4)-7g= | | (x^2+3)+(3x^2-x)-(6+5x)= | | x(3x+4)-90x=0 | | 7-3y=2/x | | (x^3)+(3x^2-x)-(6+5x)= | | 4*x-8=20 | | 6x-2(x-2)=4(x+1)+4 | | 2cosx/5=0 | | 20x^3/60x | | 7+9(4x-3)=88 | | 2(6x+4)-7(4+5x)=3 | | 4x+7+8x+11+90=180 | | 9t*3+t+5(t-9t*3)= | | -6=2cx | | 1/3x5/9=2/9 | | 1/3x5/9= | | 5x-1+5(7x+3)= | | 8(8+4r)-2(2r+2)=-52 | | 5a-4=3a+34 | | 5a-4=3a-34 | | =(3x-9)(3x-9)(3x-9)(3x-9) | | 0=7x^4-2x^2+1 | | -2p+7=-6 | | 0.40x+0.05(2-x)=0.10(22) | | f(x)=3x^2+4x-10 | | 2-(x-11)=5(x+7) | | 5x+36=96 | | -1.54=x-2.9 | | 5-3x=2(x+10) | | 2-(x-8)=5(x+11) |